Causation in different scientific disciplines: A comparison of standards in occupational medicine and particle physics - Jack Rennie Dale (Nofer Institute of Occupational Medicine, 2023)
Occupational medical research involves the collection and analysis of data to draw conclusions about the causes and prevention of workplace injuries and diseases. However, there has been criticism that some studies lack rigour in determining causation. This article examines the similarities and differences between occupational medical research and particle physics in terms of their approach to hypothesis testing, statistical methods, and confounder control. The article also explores the use of criteria such as the Bradford Hill criteria to determine causation in occupational medical research. While particle physics is often viewed as a highly rigorous science, occupational medical research also employs rigorous scientific methods to ensure findings are accurate and reliable. However, there is room for improvement in determining causation in occupational medical research, particularly in the use of criteria such as the Bradford Hill criteria to guide the development of more robust studies. It is essential for occupational medical research to adhere to rigorous scientific methods to deliver findings that can help reduce workplace injuries and diseases. The use of criteria such as the Bradford Hill criteria can ensure that the conclusions drawn. Med Pr Work Health Saf. 2023;74(4):333-9.